Development of a motorized skateboard prototype - Zamanhuri, Nurzarifah Athirah; Md Isa, Kamariah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
According to findings, many individuals in the community are concerned about the safety of skateboards, which may reach high speeds and are sometimes difficult to manage. To address these issues, a novel motorized skateboard was proposed so that it can be more closely controlled, if not outright outlawed, to safeguard the safety of riders and pedestrians. Hence, this project aims to design and fabricate a motorized skateboard. The prototype of the motorized skateboard consists of a motor, battery, wheels, deck, and speed control. The axle has two wheels at the front and back that will connect to a deck but one of the axles has a motor and timing pulley that connect to it so that the wheels can rotate automatically by the motor. Other than that, to move the motor and speed control, a 12V 1.3AH battery that generated as a power source to the motor so that it can move the skateboard.